2008
DOI: 10.1128/mcb.00507-07
|View full text |Cite
|
Sign up to set email alerts
|

αPIX Rho GTPase Guanine Nucleotide Exchange Factor Regulates Lymphocyte Functions and Antigen Receptor Signaling

Abstract: ␣PIX is a Rho GTPase guanine nucleotide exchange factor domain-containing signaling protein that associates with other proteins involved in cytoskeletal-membrane complexes. It has been shown that PIX proteins play roles in some immune cells, including neutrophils and T cells. In this study, we report the immune system phenotype of ␣PIX knockout mice. We extended ␣PIX expression experiments and found that whereas ␣PIX was specific to immune cells, its homolog ␤PIX was expressed in a wider range of cells. Mice l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 64 publications
0
58
0
Order By: Relevance
“…We previously reported that aPix 2 mice on a mixed C57BL/6 and 129Sv background have normal numbers of thymocytes, including CD4 + CD8 + DP thymocytes and CD4 + or CD8 + SP subsets, and reduced numbers of peripheral T cells (12). However, defects affecting thymocyte development are often masked by redundant homeostatic mechanisms to ensure sufficient numbers of thymocytes and T cells (1).…”
Section: Impaired Positive Selection In Tcr-transgenic Apix -Micementioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that aPix 2 mice on a mixed C57BL/6 and 129Sv background have normal numbers of thymocytes, including CD4 + CD8 + DP thymocytes and CD4 + or CD8 + SP subsets, and reduced numbers of peripheral T cells (12). However, defects affecting thymocyte development are often masked by redundant homeostatic mechanisms to ensure sufficient numbers of thymocytes and T cells (1).…”
Section: Impaired Positive Selection In Tcr-transgenic Apix -Micementioning
confidence: 99%
“…In transwell migration assays, aPix 2 T and B cells show increased chemokinesis and increased chemotaxis (12). To determine whether aPix 2 thymocytes also show increased migration in vitro, we measured the transwell migration of all thymocyte subsets (DN, DP, CD4 + SP, and CD8 + SP) to CXCL12 (also known as SDF-1) and CCL25 (also known as TECK).…”
Section: Increased Migration Of Apix -Thymocytes On 2d Surfacesmentioning
confidence: 99%
See 3 more Smart Citations